Epidemiological Studies of Polyparasitism and Associated Risk Factors in Women in Igede Land - P. O. Uweh; E. A. Omudu (Research Developments in Medicine and Medical Science Vol. 1, 2023)
The present study investigate the epidemiological perspectives of polyparasitism in Women of Reproductive age in Igede land of Benue State, Nigeria. Polyparasitism is still one of the most pressing public health issues, with one-third of the world’s population thought to be infected. Furthermore, women are of particular concern because of their gender roles, which is sensitive because ill health and/or the illness of family members generally represent greater burdens for poor women than poor men. A cross-sectional study design was adopted for this study. Fresh stool, urine and blood samples were collected from women in Igede Land of Benue State and processed for internal parasites, urine parasites and malaria parasite respectively from September 2019 to August, 2021 using systematic random sampling technique. The overall rate of polyparasitism is this study was 3.50% while a prevalence of 33.50% was recorded for single parasitic infection. The dominant parasite was Plasmodium spp. (52.16%) while the least was Strongyloides stercoralis (1.44%). Parasite combination involving Schistosoma haematobium and Malaria parasite recorded highest prevalence (36.11%) while least prevalence was recorded for coinfection with Hookworm, Entamoeba histolytica and Asccaris lumbricoides (8.33%). Also, associated factors of excretion and water source were significant (P<0.05) while meat consumption and sanitation were not significant P>0.05). Women who utilize rainwater recorded highest prevalence rates (10.60%) while the least prevalence was recorded among women who use well other sources of water (1.70%). For meat consumption, women who consume pock the most recorded the least prevalence of infection (2.10%) while those who consume goat meat recorded the highest prevalence of infection (4.60%). Also, women who use other means of sanitary disposal recorded least prevalence of infection with polyparasites while those who utilize garbage pits recorded the highest prevalence of infection (4.80%). Polyparasitism among women in Igedeland of Benue State is relatively low with malaria parasite being the most dominant parasite. It is suggested that the women of Igede land be educated on the health risks associated with polyparasitism. In addition, the government should provide free insecticide-treated nets and other antihelminth drugs to infected women in order to help reduce the burden of polyparasitism in the study area.